Epidemiological Research Advances in Vascular Calcification in Diabetes - Haipeng Yao; Zhen Sun; Guangyao Zang; Lili Zhang; Lina Hou; Chen Shao; Zhongqun Wang (Journal of Diabetes Research)
Vascular calcification is the transformation of arterial wall mesenchymal cells, particularly smooth muscle cells (SMCs), into osteoblast phenotypes by various pathological factors. Additionally, vascular transformation mediates the abnormal deposition of calcium salts in the vascular wall, such as intimal and media calcification. Various pathological types have been described, such as calcification and valve calcification. The incidence of vascular calcification in patients with diabetes is much higher than that in nondiabetic patients, representing a critical cause of cardiovascular events in patients with diabetes. Because basic research on the clinical transformation of vascular calcification has yet to be conducted, this study systematically expounds on the risk factors for vascular calcification, vascular bed differences, sex differences, ethnic differences, diagnosis, severity assessments, and treatments to facilitate the identification of a new entry point for basic research and subsequent clinical transformation regarding vascular calcification and corresponding clinical evaluation strategies.